S114 Use of front-door thoracic ultrasound to predict and improve outcomes in pleural infection in patients with community-acquired pneumonia. (11th November 2022) - Bhatnagar, M; Chamberlin, N; Rahman, NM; Stanton, AE
Abstract : Introduction: The incidence of parapneumonic effusions (PPE) in patients with community acquired pneumonia (CAP) is 20–57%, of which 5–10% develop into pleural infection. The role of early identification of PPE by thoracic ultrasound (TUS) and other presenting features in prediction of subsequent pleural infection is not clear. We explored the use of TUS in the front-door assessment of patients with CAP, particularly if this aided earlier identification of pleural infection. Methods: Consecutive patients admitted with CAP underwent TUS within 24 hours of admission. Appropriate sampling was performed in patients with effusions >2 cm depth. Final outcome including any subsequent development/worsening of effusion was recorded. CAP was defined as an 'acute respiratory febrile illness with new consolidation on Chest X-Ray (CXR) or CT scan and not attributed to COVID-19'. Results: Over a 4-week period, 39 patients with CAP were admitted, age range 40 to 90, median 74. 25/39 (64%) had a detectable pleural effusion on TUS, of which 19 (48.7%) had no visible effusion on the corresponding CXR. Most of these effusions were not amenable to sampling. Of the 6/39 (15.3%) patients who had a visible effusion on CXR, 3 were sampled, 1 of which was proven to be pleural infection. 2 patients that had a detectable effusion on TUS but not on CXR at admission subsequently developed an effusion visible on CXR. Of these, 1 patient was very unwell and died prior to sampling of pleural fluid whilst the other was discharged home without sampling. Conclusions: The incidence of PPEs may be higher than previously estimated from previous cohorts where TUS was not used in routine assessment. The characteristics of this cohort which are associated with either resolution or development of pleural infection are not understood and warrant further evaluation. Our data from this small pilot evaluation did not identify any particular TUS features that predict development of pleural infection. A detailed prospective evaluation of the use of TUS in patients with pneumonia to further characterise the natural history of PPEs is required.